Reactivaion of immune-related colitis during targeted therapy in a patient with metastatic cutaneous melanoma - E. A. Degtiareva; S. A. Protsenko; E. N. Imyanitov; G. M. Teletaeva; D. Kh. Latipova; A. I. Semenova; A. V. Novik (Сибирский онкологический журнал, 2022)
Background. The development of unique immune-related adverse events (irAEs) is a known hallmark of immunotherapy. Generally, such complications occur during the first 3–6 months of immunotherapy, however, the experience with immune checkpoint inhibitors (ICIs) shows that irAEs can also occur after completion of ICI therapy, as well as during other anticancer treatment regimens. Description of the clinical case. We present a clinical case of a patient with metastatic cutaneous melanoma, who had recurrent events of grade 2 immune-mediated diarrhea during the 2ndline of therapy. After completion of the course of immunosuppressive therapy with systemic glucocorticoids, irAE resumed, and mesalazine and budesonide (local steroid) with subsequent dose reduction were prescribed. Maintenance anti-inflammatory therapy and re-induction of targeted therapy with BRAF- and MEK-inhibitors due to the progression of the disease resulted in the reactivation of immune-mediated colitis. The complication was successfully managed by increasing dose of local steroid to full dose. Anticancer therapy was continued at the same regime without recurrent episodes of irAEs. Conclusion. When changing the anticancer treatment regimen, the recurrence of irAEs dictates careful monitoring of toxicity and the importance of timely selection of the optimal treatment algorithm to improve the quality and longevity of cancer patients.